2021
DOI: 10.1186/s12891-021-04516-x
|View full text |Cite
|
Sign up to set email alerts
|

The protective mechanism of SIRT1 on cartilage through regulation of LEF-1

Abstract: Background Osteoarthritis (OA) is a chronic degenerative disease that suppresses middle-aged and older people worldwide. Silent information regulator 1(SIRT-1) is associated with several age-related diseases, such as cardiovascular diseases, neurodegenerative diseases and tumors, etc. The protective role of SIRT-1 in bone and joint diseases has become increasingly well known. Objective To explore the relationship between SIRT-1 and its related fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The results of the present study demonstrated that Met not only acts on cartilage, but also exerts effects on the function of subchondral bone. Hu et al [ 44 ] demonstrated that pathological manifestations of advanced OA occurred 8 weeks following surgery in a mouse OA model induced by DMM surgery. The results of the present study demonstrated that mice developed subchondral osteosclerosis 8 weeks after DMM surgery, and Met maintained the normal physiological structure of the subchondral bone by relieving the occurrence of advanced subchondral osteosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that Met not only acts on cartilage, but also exerts effects on the function of subchondral bone. Hu et al [ 44 ] demonstrated that pathological manifestations of advanced OA occurred 8 weeks following surgery in a mouse OA model induced by DMM surgery. The results of the present study demonstrated that mice developed subchondral osteosclerosis 8 weeks after DMM surgery, and Met maintained the normal physiological structure of the subchondral bone by relieving the occurrence of advanced subchondral osteosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT family is a group of antiaging genes ( 108 ) that are closely associated with the aetiology of degenerative bone disease ( 109 ). Studies have demonstrated that metformin inhibits IL-1β-induced oxidative and osteoarthritic inflammatory changes by enhancing the SIRT3/PINK1/Parkin signalling pathway.…”
Section: Metforminmentioning
confidence: 99%